2016 UEFA European Championship: Pass and shot association - Bostanci, Ö.; Mayda, H.; Ceylan, L.; Kaplan, A.; Satici, A.; Yazici, Ö. F. (Journal of Human Sport & Exercise, 2018)
The purpose of this study is to analyze the association between technical features such as goal, pass, shot, ball possession and ball stealing and the goals scored in matches played by teams who qualified out of the group (n=16) and who could not (n=8) in 2016 UEFA European Championship. The data of the study were obtained by using computerized multiple camera surveillance system (Prozone). SPSS 22.0 program was used for the statistical analyses of this study. Independent T test was used to compare the parameters of teams who qualified out of the team and those who could not, while Pearson correlation analysis was used to analyze the association between variables. When the total shot parameters per match apart from shots, total pass, total pass to the third zone and ball stealing total data were compared, significant difference was found (p<0.05). In all of the shot parameters, especially in total goals scored and total shots on target (r=0.903), a positive high association was found in total ball stealing (r=0.796), total pass (r=0.753), total forward pass (r=0.819) and total pass to the third zone (r=0.748), while a negative intermediate association was found in average pass length per match (34+M) (r=-0.449). When the results were examined, it can be said that the teams who qualified out of the game can use technical properties effectively. It can be stated that in order to be successful in elite tournaments in the world, analysis practices should be taken more into consideration as well as technical and tactical practices.